Transformasi Pembayaran Digital: Edukasi QRIS dan EDC Pada UMKM di Pasar Karah - Ella Rahma Putri; M. Taufiq; Kiky Asmara (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
In the era of digital transformation, information and communication technology is developing rapidly, particularly within the economic sector. The economy is closely related to finance, resulting in innovations in financial technology within the payment system. Payments are shifting from cash to non-cash transactions. This transition is having an impact on MSMEs that are finding it difficult to adapt due to their low financial literacy. The community service programme for MSMEs aims to improve their understanding of digital finance and encourage them to use digital payments. This community service was carried out at Karah Market in collaboration with BSI KCP Pasar Grosir, involving 25 traders. This research used the PAR (Participatory Action Research) method. Through a series of socialisation activities, the programme provided an understanding of digital payment methods, such as QRIS and EDC, and demonstrated how to use them. The results showed that MSMEs in Karah Market had a better understanding of digital finance, and that the use of QRIS and EDC for digital payments increased. This makes transactions and reporting more efficient and eliminates the need for change or the risk of losing money, while providing easy access to banking services. However, continuous assistance is needed to optimise the use of digital payments (QRIS and EDC) and achieve digital financial inclusion.